Agreements from another era : production sharing agreements in Putin's Russia, 2000-2007 - Fenton Krysiek, T (Oxford Institute for Energy Studies, 2007)
Every so often a company signs an agreement so advantageous it becomes part of corporate lore and is analyzed in business school textbooks for years to come. In 1994, a consortium of foreign oil companies known as the Sakhalin Energy Investment Corporation (SEIC) believed it had signed just such a deal with the Russian government for the development rights to the Sakhalin-2 oil and gas fields in the Russian Far East (RFE). SEIC’s former CEO Steven McVeigh claimed in a Harvard Business School case study that the production sharing agreement (PSA) for Sakhalin-2 included the ‘best PSA terms that you will ever get in Russia’.1 Twelve years later, Russian President Vladimir Putin summoned the CEOs of SEIC’s remaining partners—Shell, Mitsui and Mitsubishi—to the Kremlin and forced them to sell a controlling stake in Sakhalin-2 to Gazprom, Russia’s state-owned gas company.